The Zero-Hour City: Writing London in the End Times. Issue 2 (2nd July 2020) - Charlton, Ed
Abstract : The zero-hour arguably marks much more than a form of precarious employment. Making liquid the injustice of the here and now, it also postpones any reckoning with the temporal, spatial and, more often, racial dispossessions of a city like London in this, its contemporary neoliberal progress. In this article, I offer up a reading of the zero-hour as it emerges within the city's much longer end time imagination. But I also attempt to trace an immanent critique of this tradition. Turning to the black British poet D.S. Marriott and his latest collection, Duppies (2018 ), which is best characterized as an elegy for the end of Grime, this article theorizes the possibility for a melancholy writing of London that might resist its many end time dispossessions.